No Evidence for Dystonia-Like Sensory Overflow of Tongue Representations in Adults Who Stutter - Vreeswijk, Sarah M. E.; Hoang, T. N. Linh; Korzeczek, Alexandra; Neef, Nicole E.; Wolff von Gudenberg, Alexander; Paulus, Walter; Sommer, Martin (Frontiers in Human Neuroscience, 2019)
Persistent developmental stuttering (PDS) disrupts speech fluency in about 1% of adults. Very little is known on the integrity of sensory representations of speech organs in PDS, even though many models of speech production assume an intact sensory feedback from speech organs to the brain. Here we studied somatosensory evoked potentials in adults who stutter, with the aim of probing the integrity of sensory pathways. In addition, we tested the processing of dual sensory input, to address a putative link between stuttering and focal dystonia. In 15 adults who stutter (AWS, aged 15-55 years; 3 females) and 14 matched fluent speaking adults (ANS), we recorded somatosensory evoked potentials (SEPs) at C5' and C6' induced by stimulating separately or simultaneously the tongue or the cheek at the corner of the mouth. We determined latencies (N13, P19, and N27) and peak-to-peak amplitudes (N13-P19, P19-N27). We divided amplitudes from simultaneous stimulation by the sum of those from separate stimulation. Amplitude ratios did not differ between groups, indicating normal processing of dual sensory input. This does not support a clinical analogy between focal dystonia and persistent stuttering. SEP latencies as a measure of transmission speed in sensory pathways were significantly shorter in stuttering subjects than in fluent speaking participants, however, this might have been related to a trend for a height difference between groups, and was not confirmed in a replication dataset. In summary, we did not find evidence for dystonia-like sensory overflow of tongue representations in AWS.